(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
This article is devoted to comparison of phraseological units with component zoonym “cow” and “bull” in two genetically different languages: Uzbek and English. Names of animals in the structure of phraseological expressions are connected with anthropocentric aspect. They demonstrate character, temperament, behaviour, appearance of person